Semipermeable encapsulation of calcium hydroxide for thermochemical heat storage solutions. (15th May 2017) - Afflerbach, S.; Kappes, M.; Gipperich, A.; Trettin, R.; Krumm, W.
Graphical abstract: Highlights: An approach for semipermeable encapsulation of a cohesive powder is presented. Criteria for the selection of suitable encapsulation materials are derived. Thermochemical cyclability of the encapsulated material is proven by thermal analysis. Mechanical stability of the granulated material is significantly enhanced. Abstract: Thermochemical heat storage concepts offer a promising contribution to an efficient, economic and sustainable future energy supply. One of the most considered reaction systems for Concentrated Solar Power (CSP) applications is the system CaO/Ca(OH)2 . In contrast to the cost efficiency and good availability of this material, its poor powder properties advise to complex and therefore costly reactor solutions. Thus, this work presents an approach for the design of the storage material as an adaption to its utilization in moving bed reactors. Options for particle size stabilization are discussed and criteria for the selection of encapsulation materials are derived. In order to prevent agglomeration of the cohesive storage material powder during thermochemical cycling by stabilization of the particle size in the micrometre-range, a method for a novel encapsulation of pre-granulated Ca(OH)2 with a ceramic shell is developed. To ensure the required transport of steam through the shell material, a semipermeable ceramic material is investigated. Basic physical material properties of the encapsulated storage material are determined and compared to the granulated Ca(OH)2 and to the ceramic as reference materials. By investigation of the porosity and the microstructure of the encapsulated storage material, it is shown that by the encapsulation process a porous and throughout closed shell around the storage material is formed. Thermochemical cyclability over ten reaction cycles is proven by thermal analysis. The elemental phase composition is examined qualitatively and quantitatively before and after thermochemical cycling, giving the storage material content and information about possible side products. As expected, a loss in storage capacity of the storage material is not observed. Considering the overall sample mass, the specific storage capacity is lowered correlative to the amount of inert ceramic capsule material. By measurements of the crushing strength (CS) it is shown, that upon ceramic encapsulation, the mechanical stability before and after thermochemical cycling is significantly increased.